Herbal medicinal products in RESPIRATORY diseases – STANce of the Polish PHYTOtherapy Association – STANPHYTO RESPIRATORY I - Doniec, Zbigniew; Krauze-Baranowska, Mirosława; Czerwionka-Szaflarska, Mieczysława; Kuchar, Ernest; Fecka, Izabela; Sybilski, Adam; Woroń, Jarosław; Mastalerz-Migas, Agnieszka (Family Medicine & Primary Care Review, 2023)
Acute respiratory infections are the most common reason to seek medical attention in primary care. The infections are mostly of viral aetiology, and preparations containing herbal substances are used in symptomatic treatment. This paper reviews single and combination herbal medicinal products used for dry and wet (nonproductive and productive) cough. The therapeutic effects of individual herbal substances are discussed regarding the presence of specific biologically active compounds, taking into account the results of clinical and application studies.